2011
DOI: 10.1615/plasmamed.2013006439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2O2 and Low pH Produced by Gliding Arc Discharge on the Inactivation of Escherichia Coli in Water

Abstract: The efficacy of gliding arc (GA) discharge for the generation of hydrogen peroxide (H 2 O 2) and water with a low pH was studied because H 2 O 2 combined with low-pH environment is known as a strong oxidizer that can be used for the bacterial inactivation. The ability of the GA discharge to inactivate Escherichia coli in water was tested experimentally, and the inactivation was found to increase with the plasma treatment time and rate of water injection flow to the GA discharge system. The best result showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…No major difference in acidity levels for positive and negative energization was observed. A similar decrease in the pH of water treated with plasma was reported in [14][15][16], and this increase in acidity of plasma-treated samples may be explained by the production of H + ions. One mechanism of production of these ions is dissociation of water molecules, (Eq.…”
Section: Ta Solution Treated In Non-conductive Dishessupporting
confidence: 74%
See 1 more Smart Citation
“…No major difference in acidity levels for positive and negative energization was observed. A similar decrease in the pH of water treated with plasma was reported in [14][15][16], and this increase in acidity of plasma-treated samples may be explained by the production of H + ions. One mechanism of production of these ions is dissociation of water molecules, (Eq.…”
Section: Ta Solution Treated In Non-conductive Dishessupporting
confidence: 74%
“…The hydroxyl radical can be formed through different mechanisms, including direct electronic excitation of water molecules and dissociative recombination of exited water molecules, [13][14][15] Other mechanisms of formation of the hydroxyl radical in plasma-treated water solutions can involve formation and subsequent dissociation of peroxynitrous acid and/or peroxynitrite, as discussed in [31]. Peroxynitrous acid and peroxynitrite can be formed in an acidic environment through reaction between nitrite, hydrogen peroxide and H + ions; decomposition of this acid and its conjugate (peroxynitrite) base then results in formation of OH and NO2 radicals [31].…”
Section: Introductionmentioning
confidence: 99%
“…Some components of tap water may interfere with chemical reactions in PTW and reduce the amount of species responsible for the bactericidal effect. Additionally, the pH value of the tap water was higher than that of DI water (Figure 4), which may have reduced the bactericidal efficacy of tap water treated with AALCA as compared with DI water [33,43].…”
Section: Inactivation Of E Colimentioning
confidence: 99%
“…For that reason, thermal and warm plasmas could be used for irradiation of medium following the cooling of PTM and use in biomedical applications. Considering the high efficiency of arc or gliding arc discharges in the decomposition of CO 2 and other gases and the effective production of RONS, this type of discharge could also be employed for the effective generation and fast delivery of RONS to the target liquid [3,25,33,34]. There are many works on the generation of arc and discharges and other types of plasmas inside or on the surface of highly conductive liquids using various configurations and experimental conditions, however, generation of high-density plasma transferred to the surface of deionized water (DI) or other liquids with low electrical conductivity in ambient air is still challenging owing to the relatively high electric currents required for the stable generation of the discharge [10,11,18,23,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous in vitro studies have revealed significant antimicrobial effects of plasma sources based on a variety of technical concepts [e.g., dielectric barrier discharge (DBD), surface barrier discharge (SBD), corona, jet, microhollow cathode, gliding arc discharge] operating at various gas mixtures (e.g., helium, argon, air). [1][2][3][4][5][6] The antibacterial properties of cold plasmas have been reported in numerous studies and even in vivo in clinical trials. [7][8][9] In studies on mammalian cells, it was found that plasma exposure can generally influence cell detachment, migration, proliferation, angiogenesis, expression of proteins and adhesion molecules, DNA integrity, apoptosis and inactivation of cancer cells, membrane permeabilization, and blood coagulation.…”
Section: Introductionmentioning
confidence: 99%